Reaction Kinetics and Properties of Pumice-Based Geopolymer Systems Cured at Room Temperature - Kucukyildirim, Enver; Yorulmaz, Hediye; Durak, Ugur; Ilkentapar, Serhan; Uzal, Burak; Karahan, Okan; Atis, Cengiz Duran (Elsevier Sci Ltd, 2023)
This research investigated the kinetics of pumice-based geopolymer systems and their physical and mechanical properties. The effect of the Na2SiO3/NaOH ratio of geopolymer systems on the rate of heat evolution and total heat of reaction were examined via isothermal calorimetry of geopolymer pastes prepared with Na2SiO3/NaOH ratios of 2.5, 3, and 3.5. Hardened pastes were also studied with thermo-gravimetric analysis to determine weight loss. In addition, the unit weights and compressive strengths of the pastes prepared using pumice were measured. Although the hydration process starts the earliest in pumice-based geopolymer pastes with a Na2SiO3/ NaOH ratio of 2, they have the lowest total hydration temperature. Na2SiO3/NaOH ratio of 2.5 by mass, shows higher weight loss obtained from TGA results. The compressive strength of the paste sample, prepared with a Na2SiO3/NaOH ratio of 3.5 by mass, was the highest, with 36.30 MPa at 28d. Depending on the Na2SiO3/NaOH ratio, it is thought that as the amount of Na2SiO3 increases in the samples, silica gel formation increases in later ages.
Yorulmaz, Hediye/0000-0002-1015-4308; Uzal, Burak/0000-0002-3810-7263; Atis, Cengiz Duran/0000-0003-3459-329X;
Keywords: Pumice; Reaction Kinetics; Room Temperature; Geopolymer Paste